1995
DOI: 10.1523/jneurosci.15-03-02445.1995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-HT3 receptor antagonism on hippocampal theta rhythm, memory, and LTP induction in the freely moving rat

Abstract: Serotonergic brainstem projections to hippocampus are thought to preferentially target and increase, via 5-HT3 receptors, the excitability of a distinct subpopulation of interneurons that primarily regulate GABAB-mediated inhibition in the dendritic region of pyramidal cells. Hippocampal slice work suggests that the between-burst hyperpolarization caused by slow (GABAB) IPSPs plays a significant role in controlling the strength of LTP induced with theta burst stimulation. According to the above observations it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(114 citation statements)
references
References 23 publications
7
106
1
Order By: Relevance
“…The involvement of 5-HT 3 receptors in these effects, however, has not yet been investigated. In the hippocampus, the 5-HT 3 receptor-mediated increase in GABAergic network activity (Kawa, 1994) leads to decreased excitability of pyramidal cells and reduced long-term potentiation induction (Staubli and Xu, 1995;Reznic and Staubli, 1997). Our results indicate the presence of similar mechanisms in the neocortex.…”
Section: Fast Versus Slow Neuromodulator Effectssupporting
confidence: 50%
“…The involvement of 5-HT 3 receptors in these effects, however, has not yet been investigated. In the hippocampus, the 5-HT 3 receptor-mediated increase in GABAergic network activity (Kawa, 1994) leads to decreased excitability of pyramidal cells and reduced long-term potentiation induction (Staubli and Xu, 1995;Reznic and Staubli, 1997). Our results indicate the presence of similar mechanisms in the neocortex.…”
Section: Fast Versus Slow Neuromodulator Effectssupporting
confidence: 50%
“…These cells express 5-H T3 receptors which, when activated, produce a transient depolarization and discharge of action potentials that hyperpolarizes dentate granular neurons (Ropert and Guy, 1991;Kawa, 1994;Piguet and Galvan, 1994). The 5-HT3 receptor has been shown to control DG activity, and its blockade by ondansetron enhances learning and long-term potentiation (Staubli and Xu, 1995). However, it is not likely that 5-HT3 receptors are the primary receptors to be involved in the present phenomena, because ondansetron, applied peripherally or centrally, did not affect FFA action.…”
Section: Discussionmentioning
confidence: 81%
“…The discussion has emphasized cellular mechanisms and has omitted detailed consideration of the role of theta and bursting in learning and memory. A few studies have reported parallel effects of experimental manipulations on spontaneous theta rhythm in vivo and theta-burst LTP (Maren et al, 1994;Staubli and Xu, 1995). An alternative approach, showing that theta-burst stimulation in vivo produces synaptic potentiation as its behavioral significance is learned (Roman et al, 1987) was instrumental in the development of the theta-burst LTP paradigm.…”
Section: Discussionmentioning
confidence: 99%